2008
DOI: 10.1007/s00192-008-0598-7
|View full text |Cite
|
Sign up to set email alerts
|

A microbiological and immunohistochemical analysis of periurethral and vaginal tissue in women with de novo urge symptoms after mid-urethral sling procedures—a prospective case-controlled study

Abstract: The aims were to determine whether bacteria-infection-elicited immune response after mid-urethral sling (MUS) may cause de novo urge symptoms (DNUS) and to evaluate the efficacy of suburethral sling excision for relieving the urgency. In a period of 40 months, 360 consecutive subjects with urodynamic stress incontinence had undergone one of three different MUS. Sixty-eight women with DNUS were included after exclusion. The suburethral sling of 24 of the 68 women needed to be excised because of refractory urgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…We therefore believe that this is a spurious finding and that the explanation is more likely that some of the operating departments have not diagnosed all their cases of asymptomatic tape exposure, while others have carried out postoperative vaginal inspection more frequently. Except for the finding of a slight reduction in the incidence of prolonged postoperative pain in the antibiotic prophylaxis group, there is little else in our results that supports the hypothesis that chronic inflammation or low-grade infection in biofilm along the implant results in more women developing pain, vaginal wound dehiscence or persistent or de novo urgency urinary incontinence as has been suggested by others [6,7].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We therefore believe that this is a spurious finding and that the explanation is more likely that some of the operating departments have not diagnosed all their cases of asymptomatic tape exposure, while others have carried out postoperative vaginal inspection more frequently. Except for the finding of a slight reduction in the incidence of prolonged postoperative pain in the antibiotic prophylaxis group, there is little else in our results that supports the hypothesis that chronic inflammation or low-grade infection in biofilm along the implant results in more women developing pain, vaginal wound dehiscence or persistent or de novo urgency urinary incontinence as has been suggested by others [6,7].…”
Section: Discussionsupporting
confidence: 69%
“…It has been suggested that some patients develop a chronic tape-related inflammatory tissue response or a chronic lowgrade infection in biofilm along the tape that remains subclinical and undetected, but this might cause other problems such as tape exposure, de novo urgency urinary incontinence (UUI), persistent bothersome urgency symptoms and chronic pain in some cases requiring tape removal [6,7]. We hypothesized that the risk of these negative outcomes would be higher in the group without antibiotic prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, aside from infection of the implanted mesh itself, some authors suggest an infected mesh as being a key component in de novo urge symptoms after placement of a midurethral sling [31]. In that study, 83% of patients with urge symptoms had bacteria identified in the excised tissue, compared to 5% in controls.…”
Section: Bacterial Colonizationmentioning
confidence: 92%
“…Previous studies 33 indicated several factors which might contribute to the development of de novo OAB symptoms, such as nerve damage to the bladder during dissection, 35 bladder outlet obstruction, 36 or reaction to the foreign body. 37 The combination of LSC and MUS may increase the risk for the postoperative de novo OAB incidence from different etiologies.…”
Section: Resultsmentioning
confidence: 99%